2012
DOI: 10.1590/s1516-35982012000300041
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perception of Brazilian traced beef

Abstract: -The objective of this study was to determine consumers understanding of beef traceability, identifying how consumers value this meat and traceability elements to be presented on retail shelves. The method used in this study was a survey through the internet applying the Sphinx software. The sample consisted of 417 consumers, mostly living in Porto Alegre, Brazil. Consumers are aware of certified beef, consider it important, but this is not a demand. As to traced beef, most consumers (62.4%) are in favor of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 9 publications
2
15
0
15
Order By: Relevance
“…Esse é um conceito parcialmente correto, porém incompleto, pois toda carne rastreada deve passar por um serviço de inspeção realizado pelos órgãos governamentais, mas não garante que, devido a isso, a carne seja considerada um produto rastreado. Esses resultados assemelharam-se aos encontrados por Barcellos et al (2012) Para 56,82% dos entrevistados com idade inferior a 40 anos, uma desvantagem da carne com certificação de origem é que ela é considerada um produto mais oneroso do que uma carne sem certificação de origem. Mesmo assim, 82,57% desses consumidores mais jovens e 61,40% das pessoas com mais idade estão dispostos a pagar mais caro pela carne com certificação de origem.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Esse é um conceito parcialmente correto, porém incompleto, pois toda carne rastreada deve passar por um serviço de inspeção realizado pelos órgãos governamentais, mas não garante que, devido a isso, a carne seja considerada um produto rastreado. Esses resultados assemelharam-se aos encontrados por Barcellos et al (2012) Para 56,82% dos entrevistados com idade inferior a 40 anos, uma desvantagem da carne com certificação de origem é que ela é considerada um produto mais oneroso do que uma carne sem certificação de origem. Mesmo assim, 82,57% desses consumidores mais jovens e 61,40% das pessoas com mais idade estão dispostos a pagar mais caro pela carne com certificação de origem.…”
Section: Resultsunclassified
“…Assim como 70,30% dos consumidores com maiores rendas sabem o que é carne rastreada, 70,50% dos entrevistados da pesquisa de Barcellos et al (2012) também tinham conhecimento sobre a rastreabilidade. Ainda, a maioria desses entrevistados (62,40%) disse que era a favor da rastreabilidade obrigatória da carne no Brasil.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Finally, we consider the impact of product traceability on SSCM. The enhanced traceability of upstream and downstream producers can improve the production behavior of upstream and downstream producers [35]. Firms implement effective SCM to obtain high quality, low-cost competitive advantage, thus making it profitable for enterprises to enhance their sustainable performance [36].…”
Section: Hypothesis 1c(h1c)mentioning
confidence: 99%
“…It is confirmed that more than half of the interviewees do not have the practice of recording data on health or zootechnical control in the herd in each mesoregion (Table 4), with the exception of breeders in the southwest of the state, which is worrisome, since the zootechnical record is the basis for animal tracing, a legal requirement of the Ministry of Agriculture that is difficult to be met throughout the country (Barcellos, Abicht, Brandão, Canozzi, & Collares, 2012).…”
Section: Resultsmentioning
confidence: 98%